Education through human rights as an innovative right-based pedagogical approach to promote quality education: A case study in Bangladesh (Teacher’s World: Journal of Education and Research, 2023)
Policymakers and educators worldwide are continuing to pay close attention to promoting education through right-based pedagogy in schools to raise educational standards. The government of Bangladesh has paid immense attention to quality education through different policy initiatives and strategic plans, but little is known about right-based pedagogy and quality education in the Bangladesh context. This paper describes the development of right-based pedagogical techniques in supporting quality education at a government secondary school in Bangladesh using a qualitative case study approach with an action research component. Focus group discussions, semi-structured interviews, participant observation and field notes were used to collect data from the head teacher, teachers, and students. This paper seeks to advance knowledge of how Bangladesh might adopt a global framework of human rights education— ”education through human rights”—in order to provide high-quality education. Challenges and implications have also been explored.Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.131-145